ANALYSIS OF GENETIC STRUCTURALISM IN THE SHORT STORY "KEMARAU" BY ANDREA HIRATA - Wahidha, Tasya Agustina; Khairunnisa, Siti; Harahap, Wahid Gunadi; Syajida, Syajida; Sakdiani, Sakdiani (LUMBUNG AKSARA, 2023)
Genetic structuralism analysis of the short story entitled Kemarau to be studied using sociolinguistic studies. This research aims to determine genetic structuralism in the form of human facts and the author's world view of a dry short story. This research method uses a qualitative descriptive method. This type of qualitative research has a descriptive nature and leads to analysis. Descriptive research is a research method that aims to present research results. The data in this research comes from the short story entitled kemarau. The data collection technique in this research is by reading and noting technical words found in short stories. The steps taken in this research are examining the problem, collecting data, presenting the data, and drawing conclusions from the research results. The subject of this research is the short story entitled "Kemarau" by Andrea Hirata.